Inflation, stabilisation and economic recovery in Italy after the war: Vera Lutz’s assessment - MASERA, R.S. (PSL Quarterly Review, 2013)
The present work contains an overview of economic developments in Italy between the end of the war and the stabilisation measures of September 1947 in order to provide a concise factual background to examine Vera Lutz’s analysis of this period. The main elements of Lutz’s analytical framework at the beginning of the 1950s are briefly recalled. A review of her critical assessment of Italy’s immediate postwar experience and of the policies adopted, especially in the monetary and balance-of-payments areas is provided. JEL: B31, F32, E52